The different generations fermions investigation in it scattering by high energy photon beams - Shershan, Ivan A.; Shishkina, Tatiana V. (Journal of the Belarusian State University. Physics, 2017)
The paper is devoted to the investigation of differential and total cross sections of photon-fermion processes and calculation of the amplitudes of such processes. The cross sections for the scattering of photons by leptons of different generations where calculated and investigated in Lorentz-invariant form. It was discovered that the scattering cross section of photon-fermion processes decreases when the fermion’s masses were grows. These processes will be investigated on the planned International Linear Collider to test the theory of electroweak interaction to discover the effects beyond Standard Model and to construct of nonminimal gauge theory.
Keywords: scattering; cross section; Standard Model; International Linear Collider